Strategi Kepala Sekolah dalam Meningkatkan Kinerja Guru di SMK Negeri 11 Muaro Jambi - Mulyadi Mulyadi; Ahmad Hidayat; Antiyosefa Antiyosefa; M. Raditya Rizky P; Abdul Rahman; Lina Suryati (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
This study aims to find out the strategy carried out by the Principal of SMK Negeri 11 Muaro Jambi in improving teacher performance in the school. This research was carried out from October to November 2022, located at SMK Negeri 11 Muaro Jambi Regency, Jambi Province. In this study, the author used a qualitative type of research with a descriptive approach, namely the author went directly to the field. In determining the sample, there are two informant determination techniques, namely from the Nonprobability Sampling technique, which consists of Snowball Sampling and Purposive Sampling. The types of data used are primary and secondary data. Data collection techniques with interviews, observations and documentation. The results showed that the strategy carried out by the Head of SMK Negeri 11 Muaro Jambi has been carried out to improve the performance of teachers in the school. Among the things that have been done is to improve teacher discipline and provide motivation and appreciation of work for teachers.